2016
DOI: 10.1182/blood.v128.22.991.991
|View full text |Cite
|
Sign up to set email alerts
|

Upfront Single Versus Double Autologous Stem Cell Transplantation for Newly Diagnosed Multiple Myeloma: An Intergroup, Multicenter, Phase III Study of the European Myeloma Network (EMN02/HO95 MM Trial)

Abstract: Background The role of single vs double autologous stem cell transplantation (ASCT) in patients with newly diagnosed (ND) multiple myeloma (MM) needs to be prospectively investigated in the novel agent era. Methods The phase III EMN02/HO95 study was designed to compare (first randomization, R1) (stratification according to ISS stage) standard-dose intensification therapy with bortezomib-melphalan-prednisone (VMP) vs high-dose intensification therapy with melphalan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 0 publications
1
42
0
1
Order By: Relevance
“…Recently, 2 studies addressing the role of tandem ASCT have shown opposite results. The European study demonstrated superiority of tandem versus single transplantation [34], especially for high-risk patients, while the United States study by the Blood and Marrow Transplant Clinical Trials Network (BMT CTN 0702) did not show any benefit [35].…”
Section: Tandem and Multiple Transplantationsmentioning
confidence: 99%
“…Recently, 2 studies addressing the role of tandem ASCT have shown opposite results. The European study demonstrated superiority of tandem versus single transplantation [34], especially for high-risk patients, while the United States study by the Blood and Marrow Transplant Clinical Trials Network (BMT CTN 0702) did not show any benefit [35].…”
Section: Tandem and Multiple Transplantationsmentioning
confidence: 99%
“…41 Similar results have been reported in a preliminary analysis of the European EMN02/HO95 trial, in which patients who underwent tandem ASCT had a significantly higher 3-year PFS rate (74% vs 62%; P = .005) in comparison with those who underwent single ASCT. 38 To address the role of consolidation therapy after a first ASCT, the phase 3 STAMINA trial randomized patients with NDMM who previously underwent a first ASCT to either a second ASCT or RVD consolidation followed by lenalidomide maintenance. 39 At 38 months, the investigators found no differences in terms of PFS (57% vs 57%) or OS (86% vs 82%) between the 2 groups.…”
Section: Single Asct Versus Tandem Asctmentioning
confidence: 99%
“…High risk genetic features frequently result in the dysregulation of transcription factors or tumour suppressors and include t(4;14), t(14;16), t (16;20), del(17p) and copy number changes of chromosome 1, which are used for stratifying MM patients in clinical trials and are now becoming important in guiding therapy in routine practice [126]. For example, the EMN02/HO95 study demonstrated the benefit of double autologous stem cell transplantation in patient with high-risk genetics, essentially negating the adverse prognosis of high genetic risk MM [127]. Similarly, the addition of Bortezomib to induction regimens in patients receiving HDM/ASCT may partially overcome cytogenetically defined poor risk [128].…”
Section: Cytogenetics Mutation Patterns and Clonal Evolutionmentioning
confidence: 99%